2020
DOI: 10.1371/journal.pone.0227928
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression in advanced Algerian breast cancer tissues

Abstract: Breast cancer is one of the commonest cancers among Algerian females. Compared to Western populations, the median age of diagnosis of breast cancer is much lower in Algeria. The objective of this study is to explore the expression of several miRNAs reported to be deregulated in breast cancer. The miRNAs miR-21, miR-125b, miR-100, miR-425-5p, miR-200c, miR-183 and miR-182 were studied on tumor and normal adjacent Algerian breast tissues using quantitative reverse transcription real time PCR, and the results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As a circulating biomarker, it has been studied in different approaches. In a plasma-based study, it did not show diagnostic value [103]. However, it was upregulated in another study on the blood of BC patients [104].…”
Section: Discussionmentioning
confidence: 94%
“…As a circulating biomarker, it has been studied in different approaches. In a plasma-based study, it did not show diagnostic value [103]. However, it was upregulated in another study on the blood of BC patients [104].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, there is no research in the recent literature linking these two miRNAs in BC. The association of hsa-miR-200c and hsa-miR-125b has been studied in a recent work where no significant correlation between these two miRNAs was observed 48 . The hypothesis that we put forward to explain our counter-intuitive result is that in this cohort, the oncogenic function of hsa-miR-200c is stabilized by its high connection with hsa-miR-449a.…”
Section: Resultsmentioning
confidence: 99%
“…The first evidence of miRNA implication in cancer came from its deregulation in human Chronic Lymphocytic Leukemia [ 17 ]. Later accumulating evidence has demonstrated that miRNA dysregulation plays an important role in cancer progression [ 18–21 ]. For example, miR-15a-5p, miR-15b-5p, and miR-16-5p were reported to inhibit NB progression by directly targeting Neuroblastoma MYC Oncogene (MYCN) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%